Medication Errors and Safety Culture in a Norwegian Hospital - Waaseth, Marit; Ademi, Adelina; Fredheim, Mette; Antonsen, Margaret Aarag; Brox, Nina M Bjæring; Lehnbom, Elin (IOS Press, 2019)
Source at https://doi.org/10.3233/SHTI190147. Medication errors are associated with adverse health outcomes and may prolong hospital stays and increase societal costs. Safety initiatives to reduce adverse health outcomes should be based on reliable information of current shortcomings. The aim of this study was to identify barriers to medication error reporting in a hospital and to describe heath personnel’s views of the safety culture. Seven interviews with health personnel (two doctors, four nurses and one pharmacist) were conducted November 2016–January 2017 at the University Hospital of North Norway. Nurses, more frequently than doctors, reported medication errors and discussed reported errors at staff meetings. Doctors preferred to solve the problem directly, for example writing a new medication order, rather than writing a report when a medication error had been identified. There was variation between the wards regarding the perception of support, confidence in and focus on error reporting, which indicates different safety cultures within the hospital. Identified barriers to medication error reporting included lack of time, and the impression that the reporting system is complicated and not user-friendly. Staff also reported inadequate training using the system, which could contribute to the perception that the system is inaccessible. Hospital management should take actions to improve the safety culture throughout the hospital based on the barriers identified in this study. This could include stronger focus on the importance of reporting medication errors, a transparent review process and clearly communicated actions.